'A River of Knives and Swords': Ritually Deposited Weapons in English Watercourses and Wetlands during the Viking Age. (2014) - Raffield, Ben
Abstract : This paper discusses the deposition of weapons in English rivers and wetlands during the Viking Age. Such finds have been extensively studied in Scandinavia but have rarely been academically discussed in Britain. It can be argued that the arrival of the Scandinavians in ninth- to eleventh-century Britain precipitated a marked increase in depositions of a 'pagan' nature. Despite deep-rooted, institutionalized Christianity having dominated England for some time, it is possible that pagan beliefs were dormant but not forgotten, with the Scandinavian arrival triggering their resurgence. Weapons form a large number of ritual depositions, with seventy deposits being mapped geographically to identify distributional patterns across the landscape. It is suggested here that 'liminal' depositions in Viking Age Scandinavia provide an interpretative model for these finds. Given the context of endemic conflict and territorial consolidation within which they may have been deposited in England, this material can shed new light on attitudes to landscapes subject to conflict and consolidation.